Towards a national policy on nursing education and training: an imperative framework for integrating nursing education within South Africa's post-school education system - Vhothusa Edward Matahela; Nonhlanhla Jabulile Makhanya (BMC, 2024)
Abstract The aim of this study article is to present an analysis of the first national policy framework, which provides a coherent approach to integrating nursing education into a newly defined band for higher education programmes in South Africa. The significance of this policy framework is ensuring the seamless transition from legacy nursing programmes to NQF-registered nursing programmes. It explores the agenda-setting process, analyses the prevailing context and outlines the rationale for the policy. Walt and Gilson's policy triage analysis process outlines the key elements of the policy development process. Drawing upon Tarlov's two-phased public policy development process, the article outlines the steps completed in the policy development process. Recommendations are proposed to expand access, improve quality and diversify the provisioning of nursing education and training in South Africa.